Induced calving in beef cattle - V. Hultine; G.H. Kiracofe; R.R. Schalles; R.M. McKee; R.C. DeBenedetti (Kansas Agricultural Experiment Station Research Reports, 1977)
Calving was induced in 26 of 29 Polled Hereford cows that were injected between 271 and 287 days of gestation intramuscularly with 20 mgs. Of dexamethasone (Azium) and 10 mgs. ECP (estradiol cypionate). Oxytocin, give to cows that had not calved by 40 hours after dexamthasone injection, shortened the average interval to calving (15.4 hours if returned to pasture, 16.1 if in confinement compared with 32.6 hours with no oxytocin). Three cows did not respond to treatment. ECP did not reduce retained placentas; 77% of the cows induced to calve retained membranes.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen' s Day; 1977; Beef; Calving; Dexamethasone; Oxytocin